The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5539/ass.v9n13p270
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning: What Guidelines Should We Produce in the Context of Mobile Learning Implementation in the Conflict Area of the Four Southernmost Provinces of Thailand

Abstract: Existing typical room based learning in the four southernmost provinces of Thailand includes several limitations. Physical security is the key issue when making journeys to schools and universities and the destruction of physical buildings also poses concrete limitations to existing room based learning in the affected area. With this phenomenon, the accessibility to physical room based class is problematic and limited. In contrast, the accessibility to mobile networks is getting wider; accessibility to mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some scholars opine that m-learning simply means learning via mobile devices (Chang, Littman-Quinn, & Kovarik, 2013;Hyman et al, 2014;Stevens & Kitchenham, 2011). Others focus on the mobility of the learner and learning activities (Bajpai, 2011;Binsaleh & Binsaleh, 2013). Thus, many scholars prefer to use the definition provided by the MOBlearn project (O'Malley, Vavoula, Glew, Taylor, Sharples, & Lefrer, 2003), which defines m-learning by incorporating the two major ideas mentioned above, i.e., m-learning is "any sort of learning that happens when the learner is not at a fixed, predetermined location, or learning that happens when the learner takes advantage of the learning opportunities offered by mobile technologies".…”
Section: Literature Review On M-learning Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars opine that m-learning simply means learning via mobile devices (Chang, Littman-Quinn, & Kovarik, 2013;Hyman et al, 2014;Stevens & Kitchenham, 2011). Others focus on the mobility of the learner and learning activities (Bajpai, 2011;Binsaleh & Binsaleh, 2013). Thus, many scholars prefer to use the definition provided by the MOBlearn project (O'Malley, Vavoula, Glew, Taylor, Sharples, & Lefrer, 2003), which defines m-learning by incorporating the two major ideas mentioned above, i.e., m-learning is "any sort of learning that happens when the learner is not at a fixed, predetermined location, or learning that happens when the learner takes advantage of the learning opportunities offered by mobile technologies".…”
Section: Literature Review On M-learning Overviewmentioning
confidence: 99%
“…The pocket-sized mobile devices offer computer-like capabilities and Internet connectivity without restriction of time and venue (Henderson & Chapman, 2012;Little, 2011). These unique features are drawing worldwide attention to the potential of m-learning in transforming the education landscape, as learners are now feasible to access, share and create knowledge anytime and anywhere (Binsaleh & Binsaleh, 2013;Fok, 2012;Hyman, Moser, & Segala, 2014;Koole, McQuilkin, & Ally, 2010). This scenario motivates learners to actively participate in their learning, impelling a change from the traditional knowledge transmission approach to a learner-centered knowledge construction paradigm (Li, Lou, Tseng, & Huang, 2013;Shih, Hwang, Chu, & Chuang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The elements with the F/P index higher than 1 are shown in Table 2. Previous findings in psychology research showed that people's brains store information in a hieratical structure [6]. Therefore, by revealing the sequence and the times of drawing a specific element, people's cognitive processes can be traced.…”
Section: Progressmentioning
confidence: 99%
“…Diffusion of tablet teaching entails innovative instructional strategies for planning learning activities to trigger children's curiosity to learn, and motivation to search, explore, use, and communicate with diverse electronic media (Binsaleh & Binsaleh, 2013;Castek & Beach, 2013;Ciampa, 2014). Various approaches to fostering knowledge acquisition have an influence on teachers and children's perceptions in the adoption of tablets in teaching and learning (Binsaleh & Binsaleh, 2013;Blackwell, 2103).…”
Section: Change In Pedagogical Knowledgementioning
confidence: 99%
“…Facilitation conditions in the adoption process are important. Children's curiosity and motivation to use new media for learning might also have a potential impact on teachers' adoption of tablets in teaching (Binsaleh & Binsaleh, 2013;Castek & Beach, 2013;Ruyter, 2014). Note.…”
mentioning
confidence: 99%